High incidence of silent cerebral infarcts in adult patients with beta thalassemia major. Issue 144 (August 2016) - Pazgal, Idit; Inbar, Edna; Cohen, Maya; Shpilberg, Ofer; Stark, Pinhas
Abstract: Objectives: Survival of beta thalassemia major (TM) patients has improved significantly over the past few decades. Consequently, less commonly reported complications are now being recognized. An incidence as high as 60% of silent cerebral infarcts (SCI) has been demonstrated by brain Magnetic Resonance Imaging (MRI) studies in beta thalassemia intermedia (TI). The aim of this study was to determine whether regularly transfused TM adult patients experience less SCI, as compared to the incidence described in TI. Methods: In this observational study, 28 transfusion dependent TM patients, > 18 years of age underwent brain MRI studies. Results: Focal bright foci in the cerebral white matter were demonstrated in 17 (60.7%) patients; most of them had multiple lesions. Elevated serum ferritin (SF), primarily 5 years Area Under the Curve, was found to have a significant association with the presence of SCI (p < 0.031). Similar results were found when 4 patients with intact spleen and 2 patients with splenules were excluded (p = 0.027). There was no significant association between number of SCI and clinical or other laboratory parameter evaluated. Conclusions: The present study demonstrates a high rate of SCI in regularly transfused TM adult patients. Effective continuous iron chelation, preventive low dose aspirin and routine periodical brain MRI are recommended. Highlights: In TM, there is a high incidence of thromboembolic events due to hypercoagulability. High incidence (60.7%) of silent cerebral infarcts (SCI) has been shown in TM. SCI were associated with elevated serum ferritin (p < 0.031). Iron chelation, low dose aspirin & routine periodical brain MRI are recommended.